The Delayed Effect of Parental Control on the Adaptation of Men and Women in Adulthood - Yakymchuk, Borys A.; Yakymchuk, Iryna P.; Vakhotska, Iryna O.; Livandovska, Inna A.; Hychko, Yuliia V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Parental control is an integral part of parent-child relations and a traditional tool of socialization. However, numerous negative effects of parental intervention in the child’s inner world are known. This study clarifies the delayed effects of parental control and a detached parenting style. 270 men and women are aged 35-44 years filled in the questionnaires of hardiness, the sovereignty of the psychological space, and perceived behavior by the father and mother. The results confirmed the prevalence of parental control, especially its manifestations on the part of mothers about daughters. In adult women’s lives, mothers’ directiveness correlates with hostility and violation of personal boundaries as regards the body, personal territory, things, habits, social connections, and values; men noted maternal interference in the formation of sovereign habits and values. At the same time, parental non-involvement is widespread; the autonomy of fathers about children is significantly greater than mothers. Correlation analysis confirmed the assumption that parental directivity/autonomy determines the hardiness and sense of integrity of personal boundaries in adulthood. The effect of parental control in adulthood depends on the gender of the children and the parents. Maternal control is a strong negative factor for daughters, while maternal autonomy positively correlates with indicators of hardiness. Paternal control was a neutral factor for daughters. For sons, the directivity of father and mother contributes to the formation of resilience. The conclusion was made about the need for differentiation of positive and negative effects of parental control, taking into account gender positions.